Studi Deskriptif Kemampuan Membaca Anak Kelompok B ditinjau Dari Status Jender Di PAUD Segugus Kelapa Kecamatan Karang Tinggi Bengkulu Tengah - anah, usmi; Suryadi, Didik; Suprapti, Anni (JURNAL PENA PAUD, 2020)
The  purpose of this research was to describe the differences in reading ability of children in group B in terms of gender status. The population in this study were all children in group B in PAUD Kelapa cluster, Karang Tinggi District, Central Bengkulu. The research sample of 38 children was taken using total sampling. The variables in this study were gender and reading ability. The data collection technique used was a test. The data analysis technique used the Mann-Whitney formula. The results showed that the reading ability of group B children in PAUD Kelapa cluster for boys with an average of 51.30% with sufficient criteria. Whereas for girls with an average of 90.72% with very good criteria. The results of the hypothesis test for reading skills indicate that the acquisition of asymp values. Sig. (2-tailed) or P value of 0.000 <0.05, then H0 is rejected or there is a difference. So, it can be concluded that the gender factor is one of the factors that determines the reading ability of Group B children in terms of gender status in PAUD Kelapa cluster, Karang Tinggi District, Central Bengkulu.Keywords: Reading ability, gender, Children group B